2020
DOI: 10.1186/s13213-020-01596-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rehydration on transcriptome during resuscitation of desiccated Pseudomonas putida KT2440

Abstract: Purpose Pseudomonas putida KT2440 is a desiccation-sensitive bacterium that loses culturability after 15 days of air desiccation. We have previously shown that P. putida KT2440 can develop a viable but nonculturable (VBNC) state after being exposed to desiccation stress and eventually recover when desiccated cells are rehydrated for at least 24 h. Methods To determine which genes of transport, oxidation-reduction, and transcription processes could be involved in the return of P. putida KT2440 to the culturab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Within the scant literature on beneficial bacteria, there are studies on P. putida KT2440 and C. metallidurans . Transcriptomic studies of P. putida KT2440 in the VBNC state caused by desiccation stress [ 127 ] showed that six genes related to transmembrane transport and oxidation-reduction processes were upregulated. The ethylene glycol porin (PP_2662) and substrate-binding protein (PP_2676) genes could transport and degrade polyhydric alcohols, which are accumulated during desiccation stress as compatible solutes.…”
Section: Proteomics Transcriptomics and Metabolomics Of Bacterial Cel...mentioning
confidence: 99%
“…Within the scant literature on beneficial bacteria, there are studies on P. putida KT2440 and C. metallidurans . Transcriptomic studies of P. putida KT2440 in the VBNC state caused by desiccation stress [ 127 ] showed that six genes related to transmembrane transport and oxidation-reduction processes were upregulated. The ethylene glycol porin (PP_2662) and substrate-binding protein (PP_2676) genes could transport and degrade polyhydric alcohols, which are accumulated during desiccation stress as compatible solutes.…”
Section: Proteomics Transcriptomics and Metabolomics Of Bacterial Cel...mentioning
confidence: 99%
“…During the rehydration process, desiccated microorganisms show rapid changes in gene expression (Finn et al, 2013;Rajeev et al, 2013;López-Lara et al, 2020). For example, López-Lara et al (2020) reported that within 20 minutes of water addition, the expression of genes involved in phenylalanine/tyrosine catabolism in the Gram-negative bacterium Pseudomonas putida were strongly upregulated, providing carbon substrates for energy generation.…”
Section: Transitions To and From The Anhydrobiotic Statementioning
confidence: 99%
“…During the rehydration process, desiccated microorganisms show rapid changes in gene expression (Finn et al, 2013;Rajeev et al, 2013;López-Lara et al, 2020). For example, López-Lara et al (2020) reported that within 20 minutes of water addition, the expression of genes involved in phenylalanine/tyrosine catabolism in the Gram-negative bacterium Pseudomonas putida were strongly upregulated, providing carbon substrates for energy generation. In a recent metatranscriptomic study of desiccated and wetted soil microbiomes, statistically significant changes in gene upregulation (e.g., motility genes, transporter genes) and downregulation (e.g., stress-response genes, autotrophic carbon-acquisition genes) were Accepted Article observed only 10 minutes after the addition of water to desiccated soils (León-Sobrino et al, 2021).…”
Section: Transitions To and From The Anhydrobiotic Statementioning
confidence: 99%
See 2 more Smart Citations